(untitled) (Al-Aasar, 2025)
Whoever among the Muslims had the honor of accompanying Prophet Muhammad (peace and blessings be upon him) or saw him is considered a Companion (Sahabi). All the Companions hold the highest ranks of virtue and status. Their merits and excellence have been mentioned countless times in the Holy Quran and authentic Hadiths. Therefore, it is essential to have faith in their absolute integrity and noble character. It is inappropriate to discuss or delve into the disputes that arose among the Companions. Rather, one should remain silent regarding them. No one should criticize them under any pretext, as speaking ill of them is sheer misguidance. The differences between the two groups of Companions were based on independent reasoning (ijtihad), with each side believing they were on the right path. In this regard, all the Companions had reached the highest level of ijtihad, and they will not be held sinful for any mistakes in their judgments. Even if an error was made by any of them, they will still be rewarded. Though they were not infallible, they were certainly protected from all forms of evil. If any of them committed a mistake or a sin, they will be forgiven because they are the most deserving of divine forgiveness and the intercession of the Prophet. (peace and blessings be upon him)